Absolute Reticulocyte Count and Reticulocyte Hemoglobin Content as Predictors of Early Response to Exclusive Oral Iron in Children with Iron Deficiency Anemia. (22nd March 2016) - Parodi, Emilia; Giraudo, Maria Teresa; Ricceri, Fulvio; Aurucci, Maria Luigia; Mazzone, Raffaela; Ramenghi, Ugo
Abstract : We report data regarding kinetic of response to oral iron in 34 iron deficiency anemia children. Twenty-four/34 patients (70.5%) reached reference value of hemoglobin (Hb) concentration for age and sex at day + 30 from the beginning of treatment (complete early responders (CERs)), and 4/34 (12%) reached an Hb concentration at least 50% higher than the original (partial early responders (PERs)). CHr at T1 (within 7 days from the beginning of treatment) was significantly different in the different groups (22.95 in CERs versus 18.41 in other patients;p = 0.001 ; 22.42 in early responders versus 18.07 in NERs;p = 0.001 ). Relative increase of CHr from T0 to T1 resulted significantly higher in CERs than in other patients (0.21 versus 0.11, p = 0.042 ) and in early responders than in NERs (0.22 versus 0.004, p = 0.006 ). Multivariate logistic models revealed a higher probability of being a complete early responder due to relative increase of ARC from T0 to T1 [OR (95% CI) = 44.95 (1.54–1311.98)] and to CHr at T1 [OR (95% CI) =3.18 (1.24–8.17)]. Our preliminary data confirm CHr as early and accurate predictor of hematological response to oral iron.